The Effect of Lifestyle, Physical Environment, and Electronic Payment on Purchase Decisions - Kiagus Ahmad Juan Saputra; Rita Komaladewi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Coffee shops have increasingly become lifestyle spaces for millennials, serving not only as venues to enjoy coffee but also as places for socializing, working, and expressing personal identity. Understanding the factors that drive millennials’ purchasing decisions in these spaces is crucial for businesses seeking to remain competitive. This study aims to examine the influence of lifestyle, physical environment, and e-Payment on millennials’ purchasing decisions at coffee shops, while also assessing the moderating role of social factors in these relationships. A quantitative approach using Partial Least Squares-Structural Equation Modeling (PLS-SEM) was employed, with data collected from 306 millennial respondents selected through purposive sampling. A five-point Likert scale questionnaire was used, and its validity and reliability were confirmed through outer and inner model testing. Results indicate that lifestyle, physical environment, and e-Payment all significantly affect purchasing decisions. Social factors strengthen the influence of lifestyle and physical environment, but do not moderate the effect of e-Payment. The model demonstrates strong predictive power with an R² of 0.80 and a Goodness of Fit (GoF) of 0.769. The study contributes to consumer behavior literature and provides practical guidance for optimizing marketing strategies in coffee shops.